Genetic Diversity of Rabbit (Oryctolagus cuniculus) Population in South Eastern Nigeria Using Microsatellite Markers: - A. I. Adeolu; M. Wheto; V. U. Oleforuh-Okoleh; R. N. Nwose; A. S. Adenaike; A. Yakubu; E. M. Abiola; B. G. Mohammed (Tropical Animal Science Journal, 2021)
A study was conducted to estimate the diversity that exists among three rabbit populations adapted to the South-Eastern part of Nigeria. Blood samples were collected from 75 matured, mixed-sex, and unrelated three rabbit breeds selected across the zone. Eight microsatellites (Sol30, Sol33, and Sol44, Sat3, Sat7, Sat8, Sat12, and INRA) markers were used for the study. These microsatellites were uniformly distributed among rabbit genomes for genotyping. Subsequently, genetic variability within and between breeds was calculated. Allelic frequencies and Hardy-Weinberg equilibriums as well as Analysis of Molecular Variance, were also estimated using GenAlEX 6.41 software. Discriminant Analysis of Principal Components (DAPC) for the population structure of the rabbit breeds was performed in R v.3.5.0 using the R package adegenet. All the 8 loci amplified in this study were found to be 100% polymorphic, the observed allele sizes and their frequencies for the microsatellite markers in every three breeds showed that the highest frequency was 0.330 for the allele with the size of 470bp at Sol33 locus in New Zealand White (NZW) rabbits. The Nei’s genetic identities and distances between Chinchilla (CHI) and Dutch (DUT), CHI and NZW, DUT and NZW obtained in this study were [0.173, 0.185, and 0.189] and [1.753, 1.689, and 1.666] respectively. The dendrogram and biplot revealed that the three breeds were identified at two separate clusters. In addition, the admixture level of an individual rabbit among the three breeds indicated that the breeds were not pure and also the existence of more polymorphism within the breed than among the breed diversity.